THE IMPLEMENTATION OF CREATING SHARED VALUE (CSV) AND ITS IMPACT ON COMPANY’S PERFORMANCE - Tyas, Fatma Hartining; Sukoharsono, Eko Ganis (Jurnal Ilmiah Mahasiswa FEB, 2014)
The objective of this research is to analyze the implementation of CSR  toward  company’s  performance.  The CSR  is  represented  by  CSV (Creating Shared Value) and the company’s performance  is represented by  financial performance, human resource, and corporate  image.  This study employs interview as the source of primary data and company’s  report  and  publications  as  the  secondary  data. The findings  of the  study  reveals  that CSR activities  have impact toward  the  company’s performance  as shown by the  three indicators,  consisting of  financial performance, corporate image, and human resource.  From this study, it can also be concluded that the CSV activities undertaken by PT PKG a positive impact and significant enough to company performance. This is evidenced by the increasing ratio of a company's financial year, but it also PT PKG experienced  an increase in sales of their products,  it is because the PT PKG has a good image in the public  perspective. And human resources owned by PT PKG have increased as more and more human resources really have the expertise as required by the company in carrying out its activities.Keyword: CSR, CSV, and company’s  performance